2018
DOI: 10.21660/2018.43.3531
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Effectiveness of Liquid Smoke Produced From Palm Kernel Shells in Inhibiting Black Pod Disease in Cacao Fruit in Vitro

Abstract: The effectiveness of liquid smoke made from palm kernel shells in inhibiting black pod disease (Phytopthora palmivora) in cacao fruit was studied. Palm kernel shells underwent pyrolysis in a slow-pyrolysis reactor at 280°C-400°C. The resulting liquid smoke was then distilled at a temperature of 200°C. The observed parameters were incubation period and spotting diameter. The experimental design was completely randomized, with a 4 × 6 factorial pattern having four repetitions and consisting of two factors. Both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 28 publications
0
16
0
3
Order By: Relevance
“…This process occurs in various stages: (i) hemicelluloses are disintegrated at 200-315°C, resulting in formation of furan, acetic acid and its derivatives; (ii) cellulose is disintegrated at 240-350°C, resulting in carbonic acid formation; (iii) lignin is disintegrated at 280-500°C, resulting in production of phenol, phenolic ether and its derivatives 2 . In principle, any wood material can be used in pyrolysis to produce liquid smoke, including palm kernel shells, sugar cane fibers, empty fruit bunches, rice husks, and coconut peel [3][4][5][6][7][8][9][10] . Previous research [11][12][13] has shown that the liquid smoke produced from pyrolysis of palm kernel shells contained phenol, carbonyl and other acids.…”
Section: Introductionmentioning
confidence: 99%
“…This process occurs in various stages: (i) hemicelluloses are disintegrated at 200-315°C, resulting in formation of furan, acetic acid and its derivatives; (ii) cellulose is disintegrated at 240-350°C, resulting in carbonic acid formation; (iii) lignin is disintegrated at 280-500°C, resulting in production of phenol, phenolic ether and its derivatives 2 . In principle, any wood material can be used in pyrolysis to produce liquid smoke, including palm kernel shells, sugar cane fibers, empty fruit bunches, rice husks, and coconut peel [3][4][5][6][7][8][9][10] . Previous research [11][12][13] has shown that the liquid smoke produced from pyrolysis of palm kernel shells contained phenol, carbonyl and other acids.…”
Section: Introductionmentioning
confidence: 99%
“…Liquid smoke resulting from palm kernel shells at different temperatures has different compositions [22], [23]. Assessment of the chemical content in the liquid smoke was performed using Pyro-GCMS (GCMS-QP2010, SHIMADZU) based on a method developed by Guillen and Ibargoitia [10], [24].…”
Section: Liquid Smoke Chemical Contentsmentioning
confidence: 99%
“…Salah satu metode untuk memanfaatkan potensi limbah biomassa kelapa sawit di Indonesia adalah dengan cara mempirolisis limbah tersebut sehingga menghasilkan produk asap cair yang dapat digunakan sebagai pengawet nabati. Beberapa penelitian menunjukkan bahwa senyawa asap cair mengandung senyawa yang bersifat antibakteri dan antioksidan [7,11,12].…”
Section: Pendahuluanunclassified
“…Asap cair yang didapatkan merupakan grade 3. Selanjutnya asap cair dimurnikan dengan cara destilasi pada temperatur 190 o C. Proses pembuatan asap cair yang lebih detail dapat dilihat pada penelitian sebelumnya [11,14]. Senyawa atau Komponen kimia yang terdapat dalam asap cair akan diidentifikasi dengan menggunakan GC-MS berdasarkan metode yang dikembangkan oleh modifikasi Guillen and Ibargoitia [15,16].…”
Section: Metodologi Penelitianunclassified
See 1 more Smart Citation